(untitled) (Salam International Academic Journal, 2025)
Afghanistan ranks as the fourth-largest source country of refugees worldwide. The primary drivers of Afghan migration are war and economic hardship. The migration of Afghans to Pakistan began in 1979 following the Soviet invasion of Afghanistan. The aim of this study is to examine the current situation of Afghan refugees in Pakistan, identify the challenges they face, and propose possible solutions. The central research question is: What is the current status of Afghan refugees in Pakistan, and what challenges exist in this context? The findings of the study indicate that Afghan refugees enjoyed relatively favorable conditions in Pakistan during the 1980s; however, since the 1990s and continuing to the present, their situation has deteriorated significantly. Afghan refugees now face a wide range of challenges, including insecurity, limited access to education, economic hardship, lack of technical support, and various other difficulties. This research employs a descriptive-analytical approach and is based primarily on library-based sources.